2017
DOI: 10.3329/jom.v18i1.31174
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Hypothyroidism: A Review on Clinical Consequences and Management Strategies

Abstract: Abstract Abstract AbstractSubclinical hypothyroidism (SCH) is defined as an elevated serum thyroid-stimulating hormone (TSH) level with normal free thyroid hormone values. The prevalence of subclinical hypothyroidism is 3 to 8 percent in the general population, and up to 15 to 18 percent in women who are older than 60 years. It is more common in women than men, and its prevalence increases with age. Of patients with SCH, 80% have a serum TSH of less than 10 mIU/L. Management strategies including screening and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…It is characterized biochemically by an elevated thyroid-stimulating hormone (TSH) level and normal free thyroxine (FT4). Although most endocrinological references use a cutoff of TSH > 4.5 mIU/L to diagnose SCH [4], some studies have reported adverse pregnancy outcomes with TSH levels > 2.5 mIU/L [5]. Hence, the latter is considered a more appropriate cutoff level for patients with infertility or anticipating pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized biochemically by an elevated thyroid-stimulating hormone (TSH) level and normal free thyroxine (FT4). Although most endocrinological references use a cutoff of TSH > 4.5 mIU/L to diagnose SCH [4], some studies have reported adverse pregnancy outcomes with TSH levels > 2.5 mIU/L [5]. Hence, the latter is considered a more appropriate cutoff level for patients with infertility or anticipating pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…The marked feature of subclinical hypothyroidism is elevated serum TSH level with normal free T3 and T4 levels. The prevalence of SCH is 3-8% in general population and 15-18% in females [5] . 2-3% during pregnancy [6] .…”
Section: Introductionmentioning
confidence: 99%
“…The serum thyroid stimulating hormone (TSH) is more than the normal reference range and serum free thyroxine (T4) is within the reference range in SCH. [2] SCH has been long known to be associated with obstetric complications, infertility, neurological and psychiatric symptoms, hypercholesterolemia, atherosclerosis, thrombosis, cardiovascular complications, cholelithiasis, iron-deficiency anemia and other hematological disorders. [3][4][5][6] Thyroid hormones enhance erythropoiesis as they stimulate erythropoietin (EPO) via gene expression and increase proliferation of immature erythroid progenitors.…”
Section: Introductionmentioning
confidence: 99%